From crumbs to clicks: the role of product attributes in online consumers’ purchase intention for bakery products / Muhammad ‘Arif Aizat Bashir ... [et al.] - Bashir, Muhammad ‘Arif Aizat; Muzafar Shah, Aina Syazwani; Alden, Sperico Michael; Mohd Zahari, Mohd Salehuddin; Ferdian, Feri (Universiti Teknologi MARA, Terengganu, 2024)
This study investigated the impact of intrinsic and extrinsic product attributes on the purchase intention of bakery products among online consumers. Specifically, the study focused on perceived taste and quality as the intrinsic product attributes and price and online advertising as the extrinsic product attributes. The sample for the study was drawn from Malaysian online consumers, and 398 responses were successfully collected through close-ended online survey questionnaires. The findings revealed that all the investigated variables positively impacted online consumers’ purchase intention for bakery products. Furthermore, the results indicated that price was the most influential extrinsic product attribute on the purchase intention of online consumers, followed by online advertising, perceived taste, and perceived quality, respectively. Overall, the study contributes to understanding the factors that influence online consumers’ purchase intention for bakery products, particularly in the Malaysian context. These findings have important implications for marketers and online retailers, who can use this information to develop effective strategies to enhance consumers purchase intention and ultimately increase sales. Further research is needed to explore the factors influencing purchase intention in other contexts and with different product categories